Understanding User Engagement Strategies for Podcasts Videos on Youtube in Indonesia: A Study on Content Creation - Kurniawan, Yohannes; Halim, Enrico; Jennifer, Elisa; Pribadi, Fazha Aqsa; Bhutkar, Ganesh; Anwar, Norizan (JOIV : International Journal on Informatics Visualization, 2024)
COVID-19 has transformed human life by utilizing technology to obtain information. Based on Katadata.com, Indonesia ranks second in the world's highest number of podcast listeners in the third quarter of 2021, accounting for 35.6% of the total internet users. Based on YouTube user statistics from Global Media Insight, Indonesia also ranks fourth globally for the highest number of YouTube users in 2023, totaling 139 million. Thus, this study aims to examine the factors that can influence the strategy to attract the right audience in building podcast content and provide recommendations for appropriate user engagement by comparing the genres of current issues and business & finance podcasts on YouTube Indonesia. The research method used is descriptive analytics, using the open-source Netlytics tool to analyze text and automatically summarize and visualize public online conversations on YouTube. The results of this study indicate that current issue genres are more prevalent in Indonesian society, with one of the most influential factors being the topic and guests to currently viral podcasts. This study also analyzes other factors that influence user engagement. Therefore, the findings of this research can be utilized as an opportunity for companies/institutions to enhance their branding/promotion through YouTube video podcasts. This research can also serve as a reference for other podcast content creators in building and improving user engagement on their YouTube channels to attract more interest from Indonesian society.